2005
DOI: 10.1073/pnas.0502933102
|View full text |Cite
|
Sign up to set email alerts
|

Control of the segmentation process by graded MAPK/ERK activation in the chick embryo

Abstract: The regular spacing of somites during vertebrate embryogenesis involves a dynamic gradient of FGF signaling that controls the timing of maturation of cells in the presomitic mesoderm (PSM). How the FGF signal is transduced by PSM cells is unclear. Here, we first show that the FGF gradient is translated into graded activation of the extracellular signal-regulated kinase (ERK)͞mitogen-activated protein kinase (MAPK) pathway along the PSM in the chicken embryo. Using in ovo electroporation of PSM cells, we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
196
0
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(211 citation statements)
references
References 41 publications
13
196
0
2
Order By: Relevance
“…In zebrafish, the synchronization of the segmentation clock is realized by intercellular interaction via Delta-Notch signaling (11-13, 30, 31). Previous models have confirmed that this interaction successfully leads to the synchronization of oscillation among cells (24,25,30).However, previous analyses did not answer the following questions: (i) In the actual segmentation process, dynamic rearrangement of relative cell positions due to cell proliferation and movement is observed in the PSM (12,32,33). Can the synchronization of the segmentation clock be achieved and stably sustained under such random cell movement?…”
mentioning
confidence: 74%
“…In zebrafish, the synchronization of the segmentation clock is realized by intercellular interaction via Delta-Notch signaling (11-13, 30, 31). Previous models have confirmed that this interaction successfully leads to the synchronization of oscillation among cells (24,25,30).However, previous analyses did not answer the following questions: (i) In the actual segmentation process, dynamic rearrangement of relative cell positions due to cell proliferation and movement is observed in the PSM (12,32,33). Can the synchronization of the segmentation clock be achieved and stably sustained under such random cell movement?…”
mentioning
confidence: 74%
“…It is likely therefore that the Fgf8 and RA signals also participate in the regulation of Mesp2 expression. Recently, Delfini et al (36) reported an intriguing result suggesting that Fgf signaling represses Mesp expression. Using in ovo electroporation, they demonstrated that the up-regulation of Fgf in the PSM diminishes the endogenous expression of cMeso, the chick Mesp homolog.…”
Section: Biologymentioning
confidence: 99%
“…The function of the FGF8 gradient in determining the spacing of somatic boundaries is refined by a gradient of retinoic acid signaling activity that runs in the opposite direction (Diez del Corral et al, 2003;Moreno and Kintner, 2004). It has been demonstrated in the chicken embryo that the FGF8 gradient is translated into graded activation of the extracellular signal-regulated kinase (ERK)/mitogen-activated protein kinase (MAPK) pathway in the presomitic mesoderm (Delfini et al, 2005).…”
Section: Segmentation Clock: a Molecular Oscillator Operating In The mentioning
confidence: 99%